Improving competitiveness of small and medium-sized enterprises with the application of quality management system - Kutnjak, Goran (Array, 2019)
In a modern global economy, small and medium-sized enterprises (SMEs) have inviolable importance and inclusion in the overall social development and economic growth. Regarding the high share of SMEs in the total number of companies, given the number of employees and the share in export orientation, the question of SMEs existence, as well as their market share and competitiveness in the global environment, represents prime relevance to any national economy. Therefore, the issue of quality becomes a critical component of achieving competitiveness in delivering products and services to their consumers (customers.) Due to this extremely delicate issue, each company establishes and implements a systematic process relationship or a quality management system as a part of its general management mechanism. This is a reason for SMEs management to strategically decide on the challenges of introducing a quality management system; thus, to improve their competitiveness on the domestic and foreign markets, which is a very demanding, exhaustive and time absorbing process requiring detailed preparation and collective engagement. The basic reasons for applying a quality management system are apostrophised in any business objectives – improving business processes, product quality and services, increasing spending as a factor of developing higher market share, better reputation (image) and sustainable business results. Due to the measurable quantitative and qualitative attributes and features that can significantly enhance the introduction of quality management systems into practice of SMEs, numerous studies have been carried out, some of which are conducted within the last two decades. For the authors, this was an initiative to conduct a survey, within this paper, in the Primorsko-goranska county (Croatia) during the month of July 2018, in which a number of SMEs were analysed in the crucial areas of quality management systems.